Transport model study of transverse momentum distributions of (anti-)deuterons production in Au+Au collisions at sNN=14.5, 62.4, and 200 GeV - Yuan, Ying; Huang, Ziqian; Zhang, Xinfeng; Wei, Xiangzhong (Frontiers in Physics, 2022)
The transverse momentum distributions of deuterons and anti-deuterons in Au + Au collisions at sNN = 14.5, 62.4 and 200 GeV with different centralities are studied within the framework of the UrQMD model combined with the conventional phase-space coalescence model. A strong reversed correlation between R0 (the maximal relative distances between hadrons) and P0 (the maximal relative momentum between hadrons) can be seen. It is also time-dependent. The number of particles generated are inconsistent with experimental data for 40, −,60% and 60, −,80% centralities because deuterons have plenty of time to react with other particles, this effect becomes more obvious with the decrease of beam energy. Our results can quantitatively describe the STAR data for 0, −,10%, 10, −,20% and 20, −,40% centralities.